Can subthreshold micropulse yellow laser treatment change the anti-vascular endothelial growth factor algorithm in diabetic macular edema? A randomized clinical trial - Kanar, Hatice; Arsan, Aysu; Altun, Ahmet; Akı, Suat; Hacısalihoglu, Aynur (Indian journal of ophthalmology, 2020)
Purpose: To compare the efficacy of subthreshold micropulse yellow laser (SMYL) and intravitreal aflibercept injection (IAI) combination therapy with IAI monotherapy in the treatment of diabetic macular edema (DME) and to evaluate the number of injections and SMYL sessions required. Methods: This prospective study compared a group of 28 patients treated with a combination of SMYL and IAI with a group of 28 patients treated only with IAI. All patients initially received 3 monthly IAIs, and the monotherapy group was given additional injections as needed. The combination therapy patients additionally received SMYL after the loading phase. The primary outcome measures were the change in the best-corrected visual acuity (BCVA) and central macular thickness (CMT) from baseline to month 12; the secondary outcomes were the mean number of required injections and SMYL sessions. Results: In the monotherapy group, the BCVA improved from 0.38 ± 0.10 to 0.20 ± 0.10 logMAR; in the combination group, BCVA improved from 0.40 ± 0.09 to 0.17 ± 0.06 logMAR at the end of the 12th month. The CMT was reduced from 451.28 ± 44.85 to 328.8 ± 49.69 μm in the monotherapy group and from 466.07 ± 71.79 to 312.0 ± 39.29 μm in the combination group. Improvement of the mean BCVA and reduction of the mean CMT were similar in each group. The combination group required significantly fewer injections (3.21 ± 0.41 vs 5.39 ± 1.54; P < 0.001). By month 12, 75% of patients in the monotherapy group had required additional IAIs when compared with 16% in the combination group (P < 0.001). Conclusion: SMYL combination therapy demonstrated significant visual improvements in patients with DME. In the combination group, the retreatment rate and number of required injections were significantly lower compared with the IAI monotherapy group.